Simulation, characterization and analysis of silicon germanium and poly (triarylamine) heterojunction for prospective photo-devices - Nur Syafiqa Md Nasir (2023)
Silicon (Si) is a common electrical and optoelectronic materials technology in the semiconductor industry. Furthermore, transparent device applications with visible to near-infrared band absorption edge shifting are sought. Germanium (Ge) is a promising material that enhances absorption and greater carrier mobility of electronic devices. Poly (triarylamine) (PTAA) in room temperature deposition scope, and as an excellent p-type conductive polymer, it has good visible band transparency. This study initially investigated the PTAA/SiGe and PTAA/Si prospective photo device performance using Solar Cell Capacitance Simulator (SCAPS) software simulation. PTAA thin films are developed using the spin coating process, and SiGe thin films are deposited by the radio frequency sputtering method. The active SiGe morphology is varied by varying the % of Ge composition in SiGe materials and deposition time. In contrast, PTAA morphology is set with a fixed number of drops and spin coating device rotational speed. The structural, compositional, and surface characterisations are performed by x-ray diffraction, scanning electron microscopy with energy dispersive x-ray spectroscopy, and atomic force microscopy, respectively. The ultraviolet-visible spectroscopy for optical and source measurement unit (SMU-2400) instruments for current density - voltage characterizations are also investigated in this study. The SCAPS simulation of 0.3 μm SiGe revealed very high current density (48.1 mA/cm2) and the highest 8.55% photo-electrical energy conversion efficiency in contrast to similar thickness Si photovoltaic technology is revealed. Si0.8Ge0.2 has the highest 36.78 nm grain size and 52.49 μm-2 grain density and at 800 °C annealing temperature is achieved. Transparency analysis has shown that the Si0.8Ge0.2 deposited after 30 minutes is highly transparent for visible light in the wavelength range of 600-700 nm. The highest transparency of Si0.8Ge0.2 at 600 °C is realized at 87.87%. Si0.8Ge0.2 deposited is shown 5.19 rectifying ratio, while Si0.9Ge0.1 is 7.67. However, both Si0.8Ge0.2 and Si0.9Ge0.1 deposited on quartz substrate is revealed at 14.76 and 7.91 rectifying ratio respectively. From simulation result, PTAA/SiGe microstructure is shown preferable than PTAA/Si microstructure and experimental work Si0.8Ge0.2 is revealed more promising than Si0.9Ge0.1.